Interfacial bond properties between normal strength concrete substrate and ultra-high performance concrete as a repair material. (28th February 2020) - Zhang, Yang; Zhu, Ping; Liao, Zhaoqian; Wang, Lianhua
Highlights: The interfacial bond performance of the UHPC-NSC is sufficient for rehabilitation of concrete structures. Proper surface treatment and moisture degree are the major factor for the bond capacity of a UHPC-to-NSC interface. The bond strength of the UHPC-NSC interface can be evaluated by using the cohesion and friction coefficient. Abstract: Ultra-high performance concrete (UHPC) is suitable for the durable rehabilitation and strengthening of deteriorated normal strength concrete (NSC) structures due to its excellent characteristics, such as superior compressive strength, high tensile capacity, and extremely low permeability. However, a successful repair depends on whether the UHPC-NSC interface can provide good bonding performance under various applied loads and working conditions throughout its service life. In this study, the bond characteristics between the NSC substrate and UHPC layer were investigated by applying slant shear, splitting tensile, and direct tensile tests, and the interfacial bond strength and corresponding failure modes were observed. Seven studied factors, the roughness of substrate surface, UHPC age, moisture degree of substrate, curing condition of UHPC, strength of NSC substrate, bonding agent and expansive agent were included to explore their influences on the bond strengths, and the UHPC-NSC interfacial bonding enhancement mechanism. Results indicated that the UHPC overlay achieved superior interfacial bond performance for the rehabilitation of concrete structures, with the appropriate surface roughness and substrate wetness. The UHPC-NSC composite samples met the minimum requirements of the interfacial bond strengths specified in ACI 546-06 and achieved an "excellent" bonding quality. Furthermore, the friction coefficient for calculating interfacial bond strength was back-calculated according to the results obtained from the corresponding direct tensile and slant shear tests.